ANALYSIS OF SHARIA MAQASHID ON THE STATUS OF CHILDREN OUT OF MARRIAGE - Nur Saniah (Proceeding International Seminar of Islamic Studies, 2022)
This article discusses the analysis of maqashid sharia on the nasab status of children out of wedlock. In the midst of society there is still a lot of confusion about the lineage status of children out of wedlock, so this paper discusses the determination of the lineage of children out of wedlock and what is the purpose of sharia in determining it. This paper is a literature study using the istinbat al-law maqasidus shari'ah method. The research data were collected from the literature relevant to these problems. Then analyzed using descriptive analysis and content analysis. The results of the study concluded that children out of wedlock according to the perspective of Islamic law are linked only to their mother and mother's family based on the hadith of the Prophet SAW. According to the maqasid as-shari'ah perspective, the purpose of establishing the law is to maintain the existence of marriage and prohibit adultery and punish adulterers and all the consequences arising from these actions are daruriyah needs in maintaining offspring.Keywords: nasab, child out of wedlock, maqas (is shariah)